Participatory Evaluation of Tomato (Lycopersicon esculentum Mill.) Varieties Under Irrigation Condition at Abergelle Woreda, Ethiopia - Ademe Mihiretu; Melaku Asresu (Universitas Panji Sakti, 2023)
Participatory on-farm evaluation of improved tomato varieties namely;‘Melka salsa, 'Roma VF' and 'Kochero’ against the local variety was carried out in the 2019/20 irrigation season. The trial was laid on unreplicated simple plots using six farmers as replication at irrigation scheme of Saka kebele in Abergelle woreda. The experiment was intended to evaluate and demonstrate the performances of different tomato varieties for farmers, then to collect and assess their feedback. Based on the actual biological and farmers’ preference data, the analysis result underscores the better performance of improved tomato varieties over the local variety by the most yield-related attributes. The average marketable fruit yields of ‘Melka salsa, 'Roma VF', 'Kochero’, and the local variety were 4.62, 3.88, 3.64, and 3.10 ton.ha-1, respectively. The improved varieties had thus yielded an advantage of 72.38%, 37.14%, and 25.72% over the local variety in the given order. Among the improved tomato varieties, ‘Melka salsa' provided the highest fruit yield, and owing the highest score of overall preference attributes rank. The medium-sized, oval-shaped, and tasty flashed ‘Melka salsa’ tomato fruit is most liked by farmers for its less perishability, better market demand and good taste. The ‘Melka salsa’ tomato variety is therefore suggested for up-scaling for similar agro-ecologies that have irrigation schemes and production potential. The biological scientists were also advised to consider the farmers’ preference attributes and feedback as a backup for future tomato breeding studies.